2020
DOI: 10.3991/ijim.v14i04.13243
|View full text |Cite
|
Sign up to set email alerts
|

Efficient RTS and CTS Mechanism Which Save Time and System Resources

Abstract: It is a well-known fact that the forthcoming names are distinctively different: interference range, career sense, and transmission. The given paper reveals the underlying study of disengagement of a request to send (RTS)/ clear to send (CTS) dialog. It was basically adopted under the influence of both; the presence of distributed coordination function of IEEE 802.11 and a sub-layer protocol which is called media access control (MAC) protocol. The demonstration was seen when applying a type of traffic flows suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…The word "creativity" is originally a word derived from the Latin "creare" meaning creating or inventing something, so innovation here is meant to produce something new that was not produced before that. It is an intellectual activity in which the student becomes sensitive to problems, able to identify the deficiencies, gaps of information with the ability to formulate questions, formulate hypotheses about those problems, and test the validity of solutions so that he can reach original solutions that are not repeated, thinking characterized by the emergence of abundant, varied, new, original ideas [45][46][47][48]. The research relies on innovative thinking skills appropriate to mathematics, developed by Glyphord and Torrance, namely:…”
Section: Innovative Thinkingmentioning
confidence: 99%
“…The word "creativity" is originally a word derived from the Latin "creare" meaning creating or inventing something, so innovation here is meant to produce something new that was not produced before that. It is an intellectual activity in which the student becomes sensitive to problems, able to identify the deficiencies, gaps of information with the ability to formulate questions, formulate hypotheses about those problems, and test the validity of solutions so that he can reach original solutions that are not repeated, thinking characterized by the emergence of abundant, varied, new, original ideas [45][46][47][48]. The research relies on innovative thinking skills appropriate to mathematics, developed by Glyphord and Torrance, namely:…”
Section: Innovative Thinkingmentioning
confidence: 99%
“…6. Settling (multilingual), Mozabook provides compact applications, educational videos, interactive 3D samples and their readers come in many languages, and their number is constantly increasing [34][35][36]. 7.…”
Section: 2mentioning
confidence: 99%
“…The modern technology exams tools show the results without any mistake and without spending much time. Chou, Huang and Lin [10] reported that (VTA), which are using modern ways to enhance the student for learning, can decrease the lecturer workload. Lecturers take much time to correct paper quizzes, exams, grade exams, or even the explanation in the classroom.…”
Section: Introductionmentioning
confidence: 99%